Secular trends in motor abilities of Xinjiang children and adolescents aged 7–18 years from 1985 to 2019 - Zhang, Shuai; Li, Chengyue; Tarken, Almujiang-Yimitri; Li, Weiming (Frontiers in Public Health, 2024)
Objective To assessment the secular trend in physical fitness of children and adolescents aged 7–18 years in Xinjiang from 1985 to 2019. Method The data are derived from test scores of Xinjiang Chinese children and adolescents aged 7–18 years by the China National Student Health Monitoring Centre National Student Physical Fitness Monitoring in 1985, 1991, 1995, 2000, 2005, 2010, 2014, and 2019. The physical fitness indicators included speed, cardiorespiratory fitness, muscular strength, power, and flexibility. Results The overall physical fitness of Xinjiang children and adolescents aged 7–18 in Xinjiang demonstrated downward trend from 1985 to 2019. During the period from 1985 to 1995, the speed, power, and cardiorespiratory fitness improved significantly but worsened from 1995 to 2005. The pace of decline in physical fitness slowed down from 2005 to 2014. Some components of physical fitness improved, but most components of physical fitness continued to worsen from 2014 to 2019. Conclusion In conclusion, the overall physical fitness of Xinjiang children and adolescents aged 7–18 years worsened from 1985 to 2019, and some relatively positive trends have been found in recent years. Trends in physical fitness vary among children and adolescents by gender and age, and these differences should be emphasized in the development of relevant physical fitness policies as well as interventions.